Bakhtin, carnival and comic theory - Taylor, Ben (1995)
In Rabelais and His World, Mikhail Bakhtin presents us both with a theory of carnival, and with an account of the historical decline of the carnivalesque since the Renaissance. This thesis uses Bakhtin's work as a point of departure for an analysis of particular moments in the history of post-Renaissance comic theory. It is argued both Bakhtin's account of carnivalesque decline provides us with a potent framework within which to perform such an analysis, and that this in turn facilitates a thorough interrogation of, and engagement with, Bakhtin's theory of carnival. Chapter One outlines Bakhtin's theory, identifying its historical and utopian dimensions, and exploring some of the problems which it generates. Chapter Two addresses some of the methodological issues relating to a historical analysis of comic theory, and situates Bakhtin's theory of carnival in relation to recent work in the area of comic theory. The remaining chapters focus on particular comic theory texts in the light of Bakhtin's thesis. Chapter Three contrasts Kant's analysis of humour with Schopenhauer's theory, relating the former to its Enlightenment context and the latter to its Romantic context. Chapter Four explores Bergson's discussion of laughter, situating it in relation to modernism, while Chapter Five reviews Freud's theory of jokes, examining the proximity between the structures of carnival and the structures of the Freudian joke. Chapter Six focuses on a Brechtian theory of comedy, assessing its relationship with the carnivalesque tradition, while Chapter Seven attempts to update Bakhtin's thesis in relation to contemporary configurations by exploring recent arguments concerning the comic credentials of postmodern culture. It is argued in conclusion that, if post-Renaissance culture has witnessed a decline in the significance of the carnivalesque, then the trajectory of that decline has undergone' a complex series of historical shifts and reversals.